Environmental Impact of the Utilization of a Geothermal Area - Baba, Alper (İstanbul Kültür Üniversitesi Yayınları, 2004)
Geothermal energy is generally accepted as being on environmentally benign energy source. Geothermal development over the lost 40 years in world, has shown that it is not completely free of impacts on the environment. Environmental impocts are projected to limit the use of this needed energy resource. Most of high temperature of geothermal waters in the Wortd are highly mineralized with elevated levels ol orwnic (As). boron (B). cadmium (Cd) and lead (Pb) resulting in scaling and conosion. Since they are not reinjected, geothermal discharges also resulh in observed contamination of soil and weterways. Reinjection is recommended to be installed as o standard procedure to avoid these adverse impact

Jeotermal enerji genel olarak çevreye karşı iyi huylu enerji kaynağı olarak kabul edilir. Dünyada son 40 yılda jeotermal gelişmeler, bu kaynakların çevreye etkilerinin tamamen yok olmadığını göstermiştir. Bu enerji kaynaklarının sınır değerde kullanımlarının çevresel etkileri projelendirilmektedir. Dünyada yüksek sıcaklıklı jeotermal sular arsenik (As), bor (B), kadmiyum (Cd) ve kurşun (Pb) gibi minerallerce zenginleşmiştir. Yüksek minerlizasyon sonucu bu olanlarda kabuklaşma ve korozyon oluşmaktadır. Reenjeksiyonun yapılmadığı sahalarda jeotermal kaynakların deşarjı toprak ve suların kirlenmesine neden olmaktadır. Bu nedenle standartlara uygun reenjeksiyonların yapılması, Önemli derecede çevresel etkilerin giderimini sağlayacaktır.
Keywords: çevresel etki; environmental impact; jeotermal; geothermal; reenjeksiyon; reinjection; iz elementler; trace elements